PENGARUH PENGUNGKAPAN ENVIRONMENTAL, SOCIAL, GOVERNANCE (ESG) TERHADAP KINERJA KEUANGAN PERUSAHAAN (Studi Empiris pada Perusahaan Sektor Energi yang Terdaftar di Bursa Efek Indonesia Tahun 2022-2024) - Adelia Naila Karisa; Mutiara Tresna Parasetya (Diponegoro Journal of Accounting, 2026)
This study aims to analyze the effect of Environmental, Social, and Governance (ESG) disclosure on the financial performance of energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2022-2024 period. Financial performance is proxied by Return on Assets (ROA) and Return on Equity (ROE), while ESG disclosure is measured separately through environmental disclosure, social disclosure, and governance disclosure. This study uses a quantitative approach with secondary data obtained from annual reports, sustainability reports, Bloomberg, and the Indonesia Stock Exchange. The sample was selected using purposive sampling, resulting in 19 companies and 52 final observations after eliminating outliers. The data analysis method used is multiple linear regression with SPSS 29. The results indicate that environmental disclosure has no significant effect on ROA, but has a significant negative effect on ROE. Social disclosure has no significant effect on both ROA and ROE. Governance disclosure has a significant negative effect on ROA and ROE. These findings suggest that ESG disclosure in Indonesian energy sector companies has not yet been able to directly improve profitability. The results also indicate that sustainability disclosure may still be compliance-oriented and has not been fully integrated into operational strategies that generate short-term financial benefits.